Molecular aspects of the interaction between Mason-Pfizer monkey virus matrix protein and artificial phospholipid membrane - Junková, P; Prchal, J; Spiwok, V; Pleskot, R; Kadlec, J; Krásný, L; Hynek, R; Hrabal, R; Ruml, T (Proteins, 2016)
The Mason-Pfizer monkey virus is a type D retrovirus, which assembles its immature particles in the cytoplasm prior to their transport to the host cell membrane. The association with the membrane is mediated by the N-terminally myristoylated matrix protein. To reveal the role of particular residues which are involved in the capsid-membrane interaction, covalent labelling of arginine, lysine and tyrosine residues of the Mason-Pfizer monkey virus matrix protein bound to artificial liposomes containing 95% of phosphatidylcholine and 5% phosphatidylinositol-(4,5)-bisphosphate (PI(4,5)P2 ) was performed. The experimental results were interpreted by multiscale molecular dynamics simulations. The application of these two complementary approaches helped us to reveal that matrix protein specifically recognizes the PI(4,5)P2 molecule by the residues K20, K25, K27, K74, and Y28, while the residues K92 and K93 stabilizes the matrix protein orientation on the membrane by the interaction with another PI(4,5)P2 molecule. Residues K33, K39, K54, Y66, Y67, and K87 appear to be involved in the matrix protein oligomerization. All arginine residues remained accessible during the interaction with liposomes which indicates that they neither contribute to the interaction with membrane nor are involved in protein oligomerization. Proteins 2016; 84:1717-1727. © 2016 Wiley Periodicals, Inc.
Keywords: Protein Binding; simulace molekulární dynamiky; Phosphatidylcholines; Liposomes; protein-membrane interaction; covalent labelling; multiscale molecular dynamics; Molecular Dynamics Simulation; Amino Acid Sequence; mass spectrometry; Arginine; Phosphatidylinositol 4,5-Diphosphate; tyrosin; lysin; Lysine; liposomy; Viral Matrix Proteins; vazba proteinů; liposomes; barvení a značení; Tyrosine; fosfatidylinositol-4,5-difosfát; Peptides; sekvence aminokyselin; arginin; peptidy; Masonův-Pfizerův opičí virus; Mason-Pfizer monkey virus; phosphatidylinositol-(4,5)-bisphosphate; fosfatidylcholiny; Staining and Labeling; proteiny virové matrix